The potassium transporter KdpA affects persister formation by regulating ATP levels in Mycobacterium marinum - Xiaofan Liu; Chuan Wang; Bo Yan; Liangdong Lyu; Howard E. Takiff; Qian Gao (Emerging Microbes and Infections)
Mycobacterial persistence mechanisms remain to be fully characterized. Screening a transposon insertion library of Mycobacterium marinum identified kdpA, whose inactivation reduced the fraction of persisters after exposure to rifampicin. kdpA encodes a transmembrane protein that is part of the Kdp-ATPase, an ATP-dependent high-affinity potassium (K+) transport system. We found that kdpA is induced under low K+ conditions and is required for pH homeostasis and growth in media with low concentrations of K+. The inactivation of the Kdp system in a kdpA insertion mutant caused hyperpolarization of the cross-membrane potential, increased proton motive force (PMF) and elevated levels of intracellular ATP. The KdpA mutant phenotype could be complemented with a functional kdpA gene or supplementation with high K+ concentrations. Taken together, our results suggest that the Kdp system is required for ATP homeostasis and persister formation. The results also confirm that ATP-mediated regulation of persister formation is a general mechanism in bacteria, and suggest that K+ transporters could play a role in the regulation of ATP levels and persistence. These findings could have implications for the development of new drugs that could either target persisters or reduce their presence.